ASSA13-15-18 Efficacy and Safety of Bivalirudin Versus Heparin Plus Glycoprotein IIB/IIIA Inhibitors in Patients Undergoing Percutaneous Coronary Intervention: A Meta-Analysis of Randomised Trials. (29th April 2013) - Long, Jiang; Xiaoshu, Cheng; Renqiang, Yang; Yingli, Fan; Rui, Zhan; Lijuan, Hu
Abstract : Background and Objective: Recently, several randomised trials which compared bivalirudin with heparin plus glycoprotein IIb/IIIa inhibitors (GPIs) in patients undergoing percutaneous coronary intervention (PCI) had been published. The purpose of this study was to perform an up-to-date meta-analysis of randomised trials on the effectiveness and safety of bivalirudin versus heparin plus GPIs in patients undergoing PCI. Methods: All published clinical randomised trials which compared heparin plus GPIs with bivalirudin in patients undergoing PCI were included. The literature was searched by electronic databases which contained MEDLINE, Pubmed, Elsevier, Cochrane clinical trials and Clinical Trials.gov database from January 2000 to December 2011. Results: Ten randomised trials enrolling 21, 932 patients were included. Compared with heparin plus GPIs, bivalirudin associated with lower rates of major bleeding (P < 0.00001), minor bleeding (P < 0.00001), long-term mortality (P = 0.02), and short-term net clinical adverse events (P = 0.004). There was no significantly different rates of the major adverse cardiovascular events (≤30 days: P = 0.26; > 30 days: P = 0.10) and myocardial infarction events (≤30 days: P = 0.19; > 30 days: P = 0.84) between two groups. However, bivalirudn administration resulted in an increased long-term incidence of target vessel revascularization (P = 0.02) and a high trend in individual definition of revascularization (P = 0.07). Conclusions: Among the patients who undergoing PCI, anticoagulation with bivalirudin results in significantly lower rates of bleeding, long-term mortality and short-term net clinical adverse events when compared with heparin plus GPIs. Even that bivalirudin had high long-term risk of target vessel revascularization, there are no different in MACE and MI events between two groups.